Biological activities of polyphenols-enriched propolis from Argentina arid regions - Salas, Ana Lilia; Alberto, María Rosa; Zampini, Iris Catiana; Cuello, Ana Soledad; Maldonado, Luis Maria; Ríos, José Luis; Schmeda Hirschmann, Guillermo; Isla, María Inés (Elsevier, 2018)
Background: Propolis is a bioactive natural product collected by honeybees (Apis mellifera) from plant sources. Purpose: This study was undertaken to determine the effect of propolis extracts from arid region of Argentina, on the activity/expression of pro-inflammatory enzymes, and as potential free radical scavenger, antifungal and anthelmintic agent as well as to get a first insight into the polyphenolic profile of the active fractions. Study design/methods: Two propolis samples were collected in different time from hives located in Tucumán, Argentina. They are representative of the collection time of the raw material for phytotherapeutical purposes. Ethanolic extracts from both propolis were obtained. The PEEs were analyzed for total polyphenol (TP), non-flavonoid phenols (NFP) and flavonoid (FP) content followed by HPLC-DAD analysis and identification of components by HPLC-MS/MSn. The potentiality as anti-inflammatory (LOX, COX, iNOS enzymes), antioxidant, antifungal and nematicidal was determined. Results: PEEs contain high levels of TP, NFP and FP, including cinnamic acid, caffeic acid prenyl ester, caffeoyl dihydrocaffeate and caffeic acid 3,4-dihydroxyphenethyl ester, liquiritigenin, 2′,4′-dihydroxychalcone and 2′,4′-dihydroxy-3′-methoxychalcone. The PEEs in vitro reduced the activity of LOX and COX-2. Pretreatment of RAW 264.7 cells with PEEs before the induction of inflammatory state, inhibited NO overproduction and the iNOS protein expression was significantly decreased. The PEEs exhibited antioxidant, antifungal (Candida sp.) and nematicidal effect (C. elegans). Conclusion: These findings show the potential use of characterized PEEs from arid regions of Argentina as phytomedicine.